The Development Model of Human Resources at Islamic Universities in Aceh - Danial, Danial; Dewi, Nur Sari; Kafrawi, Kafrawi (Jurnal Ilmiah Peuradeun, 2021)
This study aimed to explain the development of the Human Resources model at IAIN Lhokseumawe in particular and Islamic Universities in general. The results showed that Human Resource Development at IAIN Lhokseumawe had focused on factors of trust, emotional ties, power relations, and career cycles. However, it had no discipline, did not have a platform that was designed and integrated, did not utilize the spirit of religion and culture as strong energy for the development of human resources. Therefore, IAIN Lhokseumawe is in a need of a comprehensive and futuristic human resource development model. This model was built based on HRD factors, HRD aspects, HRD methods, and HRD strategies/steps. HRD factors were emphasized on the platform designed, the work balance between employees, discipline, and the utilization of the potential of cultural plurality and Islamic spirit as an intrinsic power of human resource development. The development was carried out in an integrated and parallel way between individual development, career, organization, and performance management through flexible work arrangements, knowledge sharing, and the adoption of innovative technologies in a sustainable and strong leadership system.